"I never really thought that a virtual ride would be that good!": Experiences of participants with disabilities in online leisure-time physical activity during COVID-19. Issue 1 (January 2023) - Labbé, Delphine; Desai, Namra; Herman, Cassandra; Elder, Chelsea
Abstract: Background: The COVID-19 pandemic has exacerbated the sedentary behavior and inactivity of people, including individuals with disability, who were already less active than their able-bodied counterparts. Therefore, it is particularly important to think about how to maintain and increase their leisure-time physical activity (LTPA). Online adaptive programs may represent a useful tool to do so. However, there is a little research focused on the health impacts of online LTPA. Objective: This mixed-methods study aimed to explore the experiences of people with disabilities who participated in online adaptive LTPA along with the factors contributing to or limiting participation. Method: First, semi-structured interviews were conducted with 10 individuals participating in online adaptive LTPA offered by a community organization. Based on these interviews, a survey was developed and completed by 104 participants. Results: The results of the study suggested that people with disabilities can get a variety of physical and emotional health benefits when participating in adaptive online LTPA, including a strong social benefit. Staff attitude and knowledge as well as the staff's ability to adapt to participant needs played important roles in facilitating participation. Greater access to equipment was needed. Conclusion: This study offers insights into how online LTPA could support the health-promoting behavior of people with disabilities during the pandemic and beyond.